2008
DOI: 10.1243/09544054jem965
|View full text |Cite
|
Sign up to set email alerts
|

The finite element analysis of melt flow behaviour in micro-injection moulding

Abstract: Micro-injection moulding as a replication method is one of the key technologies for micromanufacture. The understanding of process constraints for a selected production route is essential both at the design stage and during mass production. In this research, an existing finite element analysis system is used to verify the effects of four process parameters: the melt and mould temperatures, injection speed, and part thickness. Special attention is paid to the melt flow sensitivity when filling microchannels, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…The results showed a three-dimensional (3D) analysis based on the Navier-Stokes flow model can simulate the flow behavior in micro structures accurately comparing to the findings of previous studies [1]. It was observed that the micro component was completely filled under S2, S3 and S4 conditions.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The results showed a three-dimensional (3D) analysis based on the Navier-Stokes flow model can simulate the flow behavior in micro structures accurately comparing to the findings of previous studies [1]. It was observed that the micro component was completely filled under S2, S3 and S4 conditions.…”
Section: Discussionsupporting
confidence: 60%
“…the Cross and Williams-Landel-Ferry (WLF) models [1]. The Cross viscosity model, with the WLF temperature and pressure dependence factor, is a mathematical expression that describes the shear thinning behaviour of polymers and is widely used for numerical simulations.…”
Section: Viscosity Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain T at a given level is critical for achieving the targeted effect by the applied pressure in /x-IM. In particular, an increase of melt temperature (Tb) results in a better filling and replication of microfeatures, while the use of the correct mould temperature (T^ can prevent early solidification [18][19][20]. Pontes and Pouzada designed an instmmented mould to assess the effects of the processing variables on F^.…”
Section: Introductionmentioning
confidence: 99%
“…There is a rich repository of polymer processing knowledge for injection moulding (IM), but due to scale effects such know-how cannot be employed directly in m-IM [7]. With the downscaling of part sizes, existing tool and part designs and polymer processing methods should be applied cautiously in m-IM, and some proven designs and processing strategies at the macro scale should be carefully reconsidered taking into account the scale effects [8]. In recent years researchers have focused their attention predominantly on the filling stage of the process, and have investigated the following main factors: melt temperature (T b ), mould temperature (T m ), injection speed (V i ), and injection pressure (P i ) [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%